NIR-II Upconversion Photoluminescence of Er3+ Doped LiYF4 and NaY(Gd)F4 Core-Shell Nanoparticles - Feng, Qilong; Zheng, Wenjing; Pu, Jie; Chen, Qiaoli; Shao, Wei (Frontiers in Chemistry, 2021)
The availability of colloidal nano-materials with highly efficiency, stability, non-toxicity in NIR-II range is beneficial for biological diagnosis and therapy. Rare earth doped nanoparticles are ideal luminescent agent for NIR-II range due to abundant energy level distribution. Among them, both excitation and emission range of Er3+ ions could be tuned into second biological window range. Herein, we synthesis and evaluate the growth process of ~15 nm LiYF4, NaYF4, NaGdF4 nanoparticles doped with Er3+ ions. The luminescence properties were compared, and LiYF4, NaYF4 showed stronger luminescence than NaGdF4, but the relative intensity of different peaks was different. With epitaxial growth an inert homogeneous protect layer, the surface passivation further enhanced LiYF4 about 5.1 times, NaYF4 about 6.5 times, and NaGdF4 about 167.7 times, respectively. Finally, A proper mechanism was proposed based on the emission intensity dependence on excitation power density.